Response of wild Mus musculus to baits containing essential oils: II Bromadiolone and difenacoum baits with 0.75% cinnamon oil tested in storages - Jokić, Goran; Mitrić, Siniša; Pejin, Dušan; Blažić, Tanja; Đedović, Suzana; Stojnić, Bojan; Vukša, Marina (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2018)
The effects of 0.75 % concentration of cinnamon essential oil on bait attractiveness andtotal biological efficacy of bromadiolone and difenacoum rodenticides to the house mousewere tested in practice.The experiments were conducted in storages with stable house mouse populations forwhich no resistance to anticoagulant rodenticides had been previously reported.A statistically significant difference was detected between bromadiolone and difenacoumbaits. Consumption of bromadiolone baits supplemented with cinnamon essential oil was 74 % higher than the consumption of bromadiolone baits without cinnamon oil. The average efficacy of bromadiolone baits in controlling house mice was 96 %.Cinnamon essential oil added to difenacoum baits increased bait consumption by 39 %, i.e. it was 119 % higher than the consumption of oil-free baits. The average efficacy ofdifenacoum baits in controlling house mice was 99.5 %.
Keywords: Rodenticides; Essential oils; Cinnamon; Storages; House mouse; Attractants